2016
DOI: 10.17235/reed.2016.4424/2016
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet agents and/or anticoagulants are not associated with worse outcome following nonvariceal upper gastrointestinal bleeding

Abstract: Background: Nonvariceal upper gastrointestinal bleeding emerges as a major complication of using antiplatelet agents and/ or anticoagulants and represents a clinical challenge in patients undergoing these therapies.Aim: To characterize patients with nonvariceal upper gastrointestinal bleeding related to antithrombotics and their management, and to determine clinical predictors of adverse outcomes.Methods: Retrospective cohort of adults who underwent upper gastrointestinal endoscopy after nonvariceal upper gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Interestingly, the mortality was slightly lower in the AC/APT group (8.3%) than in nonexposed group (10.3%). Similar results were observed in other studies ( 3 , 20 ). We found no significant difference in overall mortality according to sex or type of therapy.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Interestingly, the mortality was slightly lower in the AC/APT group (8.3%) than in nonexposed group (10.3%). Similar results were observed in other studies ( 3 , 20 ). We found no significant difference in overall mortality according to sex or type of therapy.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to the present study, other authors found that the most prevalent bleeding lesion was peptic ulcer, and that the most common bleeding-related agent was ASA ( 1 , 3 , 16 , 20 , 21 ). In our study, the most frequent bleeding site was gastric ulcer, confirming the decrease in duodenal ulcer bleedings over the years ( 22 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations